A critical analysis of vendor managed inventory in the grocery supply chain. (1st January 2012) - Mangiaracina, Riccardo; Melacini, Marco; Perego, Alessandro
The aim of this paper is to study the benefits and the drawbacks of vendor managed inventory (VMI) in the grocery supply chain. Despite its being the most popular approach to collaboration within supply chains, its level of adoption is still far from the expected, primarily due to the difficulty in identifying the benefits and assessing their economic value. This paper presents a simulation model in the context of a two-level supply chain (manufacturers and retailers) in the grocery industry. The model was developed in order to understand the impact of VMI on the overall costs for the supply chain players and the effect of some key variables. In particular, a 'one producer-many retailers' system was modelled in order to better assess the 'critical mass' effect on the success of VMI projects.